Changes in the distribution of male and female wages accounting for employment composition using bounds - Richard W. Blundell; Amanda Gosling; Hidehiko Ichimura; Costas Meghir (Institute for Fiscal Studies (IFS), 2004)
This paper examines changes in the distribution of wages using bounds to allow for the impact of non-random selection into work. We show that bounds constructed without any economic or statistical assumptions can be informative. However, since employment rates in the UK are often low they are not informative about changes in educational or gender wage differentials. Thus we explore ways to tighten these bounds using restrictions motivated from economic theory. With these assumptions we find convincing evidence of an increase in inequality within education groups, changes in the return to education and increases in the relative wages of women.
Keywords: 330; Lohndifferenzierung; Geschlecht; Schätzung; Großbritannien